Clinical Use and Adverse Drug Reactions of Linezolid: A Retrospective Study in Four Belgian Hospital Centers - Hélène Thirot; Caroline Briquet; Frédéric Frippiat; Frédérique Jacobs; Xavier Holemans; Séverine Henrard; Paul M. Tulkens; Anne Spinewine; Françoise Van Bambeke (MDPI AG, 2021)
In Belgium, linezolid is indicated for pneumonia and skin and soft tissue infections, but is more broadly used, due to its oral bioavailability and activity against multiresistant organisms. This could increase the risk of adverse drug reactions (ADR), notably hematological disorders (anemia, thrombocytopenia), neuropathy, or lactic acidosis. We analyzed linezolid clinical use in relationship with occurrence of ADR in Belgian hospitals and highlighted risk factors associated with the development of thrombocytopenia. A retrospective analysis of electronic medical records and laboratory tests of adult patients treated with linezolid in four Belgian hospitals in 2016 allowed the collection of ADR for 248 linezolid treatments. Only 19.7% of indications were in-label. ADR included 43 thrombocytopenia, 17 anemia, 4 neuropathies, and 4 increases in lactatemia. In a multi-variate analysis, risk factors of thrombocytopenia were a treatment duration > 10 days, a glomerular filtration rate < 60 mL/min, and a Charlson index ≥ 4. Off-label use of linezolid is frequent in Belgium, and ADR more frequent than reported in the summary of product characteristics, but not statistically associated with any indication. This high prevalence of ADR could be related to a high proportion of patients presenting risk factors in our population, highlighting the importance of detecting them prospectively.